2021
DOI: 10.48550/arxiv.2103.06812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superradiance in String Theory

Viraf M. Mehta,
Mehmet Demirtas,
Cody Long
et al.

Abstract: We perform an extensive analysis of the statistics of axion masses and interactions in compactifications of type IIB string theory, and we show that black hole superradiance excludes some regions of Calabi-Yau moduli space. Regardless of the cosmological model, a theory with an axion whose mass falls in a superradiant band can be probed by the measured properties of astrophysical black holes, unless the axion selfinteraction is large enough to disrupt formation of a condensate. We study a large ensemble of com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 90 publications
2
28
0
Order By: Relevance
“…They hold at fixed h 1,1 when moving in the Kähler moduli space by varying microscopic parameters like g s after the decay constants are written in terms of them thanks to moduli stabilisation. These results are complementary to the ones of [27,28] (see also [29] for qualitatively similar findings) which found an approximate log-normal distribution for the axion decay constants of a given CY model focusing at the tip of the stretched Kähler cone. Moreover they found that the mean value of the f θ i 's decreases when h 1,1 increases.…”
Section: Model With Arbitrary H 11supporting
confidence: 79%
See 4 more Smart Citations
“…They hold at fixed h 1,1 when moving in the Kähler moduli space by varying microscopic parameters like g s after the decay constants are written in terms of them thanks to moduli stabilisation. These results are complementary to the ones of [27,28] (see also [29] for qualitatively similar findings) which found an approximate log-normal distribution for the axion decay constants of a given CY model focusing at the tip of the stretched Kähler cone. Moreover they found that the mean value of the f θ i 's decreases when h 1,1 increases.…”
Section: Model With Arbitrary H 11supporting
confidence: 79%
“…Interestingly, they found that the mean value of f a decreases as h 1,1 increases. Our results are complementary to the ones of [27,28] since we included moduli stabilisation and worked out the distribution of f a and m a as a function of flux quanta, i.e. moving in the moduli space at fixed h 1,1 .…”
mentioning
confidence: 72%
See 3 more Smart Citations